2017
DOI: 10.1002/ppap.201700076
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure plasma treatment of agricultural seeds of cucumber (Cucumis sativus L.) and pepper (Capsicum annuum L.) with effect on reduction of diseases and germination improvement

Abstract: The paper presents the effects of plasma treatment on agricultural seeds. Cucumber and pepper seeds, widely used in agriculture, were treated using the Diffuse Coplanar Surface Barrier Discharge (DCSBD) at atmospheric pressure in ambient air. The plasma treatment (4 s for pepper, 20 s for cucumber) led to an improvement of germination and germinating power. XPS confirmed chemical changes on the seed surface. The surface morphology of the plasma treated seeds showed no evidence of structural damage. The conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 26 publications
2
83
0
1
Order By: Relevance
“…To improve seed absorption, plasma treatment is expected to have positive effect on germination. This would correlate with the published results (Bafoil et al, 2018;Štěpánová et al, 2018;Magureanu et al, 2018;Guo et al, 2018;Los et al, 2018). A 15 s plasma treatment did not affect germination but stimulated the growth parameter of the seeds of both cereals.…”
Section: Discussionsupporting
confidence: 92%
“…To improve seed absorption, plasma treatment is expected to have positive effect on germination. This would correlate with the published results (Bafoil et al, 2018;Štěpánová et al, 2018;Magureanu et al, 2018;Guo et al, 2018;Los et al, 2018). A 15 s plasma treatment did not affect germination but stimulated the growth parameter of the seeds of both cereals.…”
Section: Discussionsupporting
confidence: 92%
“…The application of the CP in agriculture is either direct (seeds or plants are in a direct contact with plasma) or indirect (seeds or plants are exposed to plasma treated/activated gas or water) . The plasma in direct contact with the seed can stimulate its germination and growth and subsequent fruit yield, change enzymatic activity in developing seeds, change secondary metabolites content, and also reduce phytopathogenic microflora from the seed surface . Plasma can also modify seed surface and change its affinity towards water to either hydrophilic or hydrophobic, that both can be beneficial .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous works have shown that non-thermal plasma is a fast, uniform, economic, effective, and eco-friendly approach for stimulating seed germination and seedling growth compared with the conventional seed pretreatment methods, e.g. ultraviolet and gamma radiation, scarification, hot water soaking, and chemical reagent treatment (Li et al, 2014; Randeniya and De Groot, 2015; Mildaziene et al, 2018; Štěpánová et al, 2018). In the last years many authors studied the stimulation of the seed germination and the plant growth by using plasma generator (Živković et al, 2004; Šerá et al, 2010; Dobrin et al, 2015; Bafoil et al, 2018).…”
Section: Introductionmentioning
confidence: 99%